2019
DOI: 10.1021/acs.nanolett.9b04373
|View full text |Cite
|
Sign up to set email alerts
|

Sonogenetic Modulation of Cellular Activities Using an Engineered Auditory-Sensing Protein

Abstract: Biomolecules that respond to different external stimuli enable the remote control of genetically modified cells. Chemogenetics and optogenetics, two tools that can control cellular activities via synthetic chemicals or photons, respectively, have been widely used to elucidate underlying physiological processes. These methods are, however, very invasive, have poor penetrability, or low spatiotemporal precision, attributes that hinder their use in therapeutic applications. We report herein a sonogenetic approach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 46 publications
(119 reference statements)
5
35
0
Order By: Relevance
“…We previously showed that exogenous expression of the C. elegans TRP-4 mechanoreceptor enables ultrasound-sensitivity in neurons that are otherwise unresponsive to ultrasound stimulation 23 . Similar ultrasound-sensitivity has also been observed in vitro in cells induced to express proteins belonging to the mechanosensitive (MSC) 24 , Piezo 25 , Prestin 26 , transient receptor potential (TRP) 21 , and TREK 27 families. We therefore hypothesized that proteins from these ion channel families and others hypothesized to have mechanosensitivity might confer ultrasound sensitivity to mammalian cells.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…We previously showed that exogenous expression of the C. elegans TRP-4 mechanoreceptor enables ultrasound-sensitivity in neurons that are otherwise unresponsive to ultrasound stimulation 23 . Similar ultrasound-sensitivity has also been observed in vitro in cells induced to express proteins belonging to the mechanosensitive (MSC) 24 , Piezo 25 , Prestin 26 , transient receptor potential (TRP) 21 , and TREK 27 families. We therefore hypothesized that proteins from these ion channel families and others hypothesized to have mechanosensitivity might confer ultrasound sensitivity to mammalian cells.…”
supporting
confidence: 61%
“…Finally, we demonstrate that hs TRPA1 can be used to selectively activate a specific cell population in vivo with ultrasound pulses (1-100 ms) from a 6.91 MHz transducer. We have not tested additional ultrasound frequencies, which may explain why our screen did not identify previously published candidates 2426 . Our data hint that ultrasound might not act as a simple stretch force on the membrane, and that channels that likewise sense other perturbations, including lipid bilayer changes, could be good candidates for sonogenetics.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Past research effort has been focused on developing sonogenetics based on mechanosensitive ion channels. One most recent study showed that an engineered auditory-sensing protein, prestin, successfully stimulated neurons in deep regions of mouse brains as evaluated by c-fos staining of ex vivo brain slices 16 . However, FUS-evoked calcium influx in HEK293T cells expressing this protein lasted for more than 100 s after a single FUS stimulation with no evidence to show the calcium influx could be turned off.…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanosensitive ion channels, for example, TREK-1 11 , MscL 12 , Piezo1 13,14 , and TRPA1 15 have been proposed as potential sonogenetic tools based on in vitro cell culture studies without in vivo validation. A most recent study showed that an engineered auditory-sensing protein (prestin) caused neurons in the mouse brain to sense ultrasound stimulation 16 ; however, this protein, which is not an ion channel, lacks the ability to control neuron activity in a temporally precise fashion. To our knowledge, there is so far no study that has identified ultrasoundsensitive ion channels for spatiotemporally precise modulation of neural activity in mammalian brains.…”
Section: Introductionmentioning
confidence: 99%